Collaborative Writing Skills Enhancement through the Use of Story Jumper: Mejora de las habilidades de escritura colaborativa mediante el uso de Story Jumper - Fajardo Rojas, Joffre Alexander; Fajardo Fajardo, Jonathan Patricio; Guarnizo Cajamarca, Johanna Elizabeth; Paqui Abrigo, Diego Fernando; Carrión Cabrera, Fausto Rodrigo (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2023)
The present research is about improving collaborative writing skills enhancement through the use of StoryJumper. The work aims to know the impact of using StoryJumper as a technological resource implemented to develop the EFL students’ collaborative writing skills. The sample was 27 English students who were enrolled in the second year of Bachillerato in a public institution of Loja. These students were divided randomly into two groups; the experimental and the control group. It was an experimental study aided by a qualitative and quantitative analysis through the use of pre-tests, post-tests, class observations, and student surveys. The instruments used to gather the data were a writing placement test, a writing achievement test, a rubric, an observation sheet, and a questionnaire. The data obtained helped to know the effectiveness of using StoryJumper in collaborative narrative writing and the students’ perceptions of using this platform. Finally, the findings revealed that the students reached a good improvement in the development of their narrative writing skills in addition to their remarkable motivation for the practice and development of their collaborative writing skills after the use of the StoryJumper.